1995
DOI: 10.1172/jci118283
|View full text |Cite
|
Sign up to set email alerts
|

Acid extrusion is induced by osteoclast attachment to bone. Inhibition by alendronate and calcitonin.

Abstract: Acid extrusion is essential for osteoclast (OC) activity. We examined Na + and HCO3 --independent H + extrusion in ratand mouse OCs by measuring intracellular pH (pH1) changes, with the pH1 indicator BCECF (biscarboxyethyl-5-(6) carboxyfluorescein) after H+ loading with an ammonium pulse. 90% of OCs attached to glass do not possess HCO3-and Na+-independent H +-extrusion (rate of pH1 recovery = 0.043±0.007 (SEM) pH U/min, n = 26). In contrast, in OCs attached to bone, the pH1 recovery rate is 0.228±0.011 pH. U/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 45 publications
(38 reference statements)
6
44
0
4
Order By: Relevance
“…Osteoclasts from 1,25-(OH) 2 D 3 -treated cultures plated on bone or dentine slices undergo a transformation to the activated phenotype, in which actin rings form, V-ATPase is polarized to the ruffled membrane, and bone is resorbed (1,2,5). In contrast, osteoclasts from identical cultures placed on glass coverslips fail to form ruffled membranes and do not have physiologically detectable plasma membrane V-ATPase (14,15).…”
mentioning
confidence: 89%
“…Osteoclasts from 1,25-(OH) 2 D 3 -treated cultures plated on bone or dentine slices undergo a transformation to the activated phenotype, in which actin rings form, V-ATPase is polarized to the ruffled membrane, and bone is resorbed (1,2,5). In contrast, osteoclasts from identical cultures placed on glass coverslips fail to form ruffled membranes and do not have physiologically detectable plasma membrane V-ATPase (14,15).…”
mentioning
confidence: 89%
“…We have previously shown that the sealing zone allows the passage of lowmolecular-weight markers like dextran-3000 (Stenbeck and Horton, 2000). In osteoclasts plated on glass, sealing might not be as effective as on dentine, because few acidify the subcellular space (Zimolo et al, 1995), thus allowing passage of high-molecular-weight markers, or endocytosis takes place at random sites because matrix-derived cues are missing.…”
Section: Directionality Of Endocytosis In Resorbing Osteoclastsmentioning
confidence: 99%
“…They act by promoting osteoclast apoptosis and inhibiting differentiation to mature osteoclasts [16,25,30,32,40,41] or by reducing osteoclast activity [2,10,11,15,31,38,40,44], either through an inhibition of farnesyl diphosphonate synthase (FPP) in the mevalonate pathway, or by otherwise inhibiting prenylation of small GTPases. The influence of bisphosphonates on bone formation is unknown, although it has been hypothesized, based primarily on studies in culture, that bisphosphonates inhibit osteoblast apoptosis [1,35,38] and may stimulate osteoblast proliferation and differentiation [18,19,23,26,41,42], leading to increased bone formation.…”
Section: Introductionmentioning
confidence: 99%